Southern Sanctuary : A Naturalist's Walk through the Seasons - Lewis, Marian Moore, 1937- (Book collections on Project MUSE., 2015)
In Southern Sanctuary, retired NASA research scientist and writer Marian Moore Lewis takes readers on a journey of discovery through the Goldsmith-Schiffman Wildlife Sanctuary, a 400-acre preserve in Madison County, Alabama. Writing in the voice of a knowledgeable friend and with accompanying color photographs, Lewis introduces plants, animals, and other wildlife that reside in the preserve's meadows, woods, and waterways-like those beloved throughout the American South. Lewis has organized this beautifully presented volume into twelve monthly chapters. She starts her year in April after the c.